# Difference between revisions of "Indecomposable"

From Cantor's Attic

(Images) |
(→Proof) |
||

(3 intermediate revisions by the same user not shown) | |||

Line 1: | Line 1: | ||

− | [[File:https://upload.wikimedia.org/wikipedia/commons/thumb/e/e6/Omega-exp-omega-labeled.svg/832px-Omega-exp-omega-labeled.svg]]An indecomposable ordinal is an ordinal that can't be expressed as the sum of two smaller numbers. | + | [[File:https://upload.wikimedia.org/wikipedia/commons/thumb/e/e6/Omega-exp-omega-labeled.svg/832px-Omega-exp-omega-labeled.svg.png|thumb|as ordinals]]An indecomposable ordinal is an ordinal that can't be expressed as the sum of two smaller numbers. |

== Form == | == Form == | ||

Line 5: | Line 5: | ||

=== Proof === | === Proof === | ||

− | Any ordinal that multiplies with a finite amount or added with anything can be expressed as the sum of two smaller ordinals. To avoid this, start with the smallest indecomposable ordinal and multiply it by \(\omega\) every time. This is the best way of finding all indecomposable ordinals. Why? It is because \(\omega^n\) is equal to \(\omega\) sums of \(\omega^ | + | Any ordinal that multiplies with a finite amount or added with anything can be expressed as the sum of two smaller ordinals. To avoid this, start with the smallest indecomposable ordinal and multiply it by \(\omega\) every time. This is the best way of finding all indecomposable ordinals. Why? It is because \(\omega^n\) is equal to \(\omega\) sums of \(\omega^{n-1}\). |

{{stub}} | {{stub}} |

## Latest revision as of 03:59, 15 April 2017

An indecomposable ordinal is an ordinal that can't be expressed as the sum of two smaller numbers.## Form

An indecomposable ordinal is in the form \(\omega^n\).

### Proof

Any ordinal that multiplies with a finite amount or added with anything can be expressed as the sum of two smaller ordinals. To avoid this, start with the smallest indecomposable ordinal and multiply it by \(\omega\) every time. This is the best way of finding all indecomposable ordinals. Why? It is because \(\omega^n\) is equal to \(\omega\) sums of \(\omega^{n-1}\).

This article is a stub. Please help us to improve Cantor's Attic by adding information.